The Impact of Informal Education Programs on the Outof- School Syrian Refugee Children in Child-Family Centers (CFCs) in Jordan - Inkheili, Rami (European Scientific Journal, ESJ, 2017)
The significance of this paper lies in shedding lights on the importance of informal education programs as catch up programs to educate those who didn’t have the opportunity to be in schools for different reasons and bridge the gap between them and their peers in schools. Although the study will show how powerful this tool is, it is also worth mentioning that more efforts should be done to enroll those children in public schools and provide them with equal access to the formal education system. This study used pre and post tests that are designed upon the expected learning outcomes from the literacy and numeracy materials prepared by the technical team at Save the Children International. The designed materials, in order to be compliant with the advancement of students in the formal education system were based on the national learning outcomes set by the Ministry of Education in Jordan. The results of the study were excellent enough to show the positive impact of the program as 100 percent of the population scored the passing score in the posttest compared to the zero percent passing the pretest in both literacy and numeracy classes. On the other hand, the study also shows how deprived Syrian children are as a result of the bloody war that harvests not only their souls, but also their future. Finally, it is also worth mentioning that the study also speaks of the pressure on Jordan’s formal education system and the need to support the Ministry of Education meeting the urgent demands of all students nationwide.